FASILITASI KEBUTUHAN ATAS PENGHARGAAN DIRI UNTUK MENDUKUNG PEMBELAJARAN KIMIA DI ERA SOCIETY 5.0 - Hanna, S. R. P; Dera, S.; Sali, A. (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
Indonesia has entered Revolution 4.0 where technology has become the basis of human life. Slowly but sure, Indonesia is entering the Society 5.0 Era characterized by (1) freedom; (2) customization; (3) scrutiny; (4) integrity; (5) entertainment; (6) speed; and (7) innovation. Society 5.0 offers a human-centered society that makes a balance between economic progress and solving social problems through a highly connected system between the virtual and real world. According to the Japanese prime minister, Shinzo Abe, explained in the World Economic Forum (WEF) that the Society 5.0 is no longer about capital, but data that connects and mobilizes all fields such as education and health that must fill the gap in society. At this time, we will propose the role of education in the Era of Society 5.0, especially related to chemistry learning that facilitates the need for self-esteem. Human needs are the same, such as basic needs, described as the hierarchy of needs by Maslow's Theory. The need for self-esteem is one of the needs of human psychology that must be fulfilled, especially for students to face the challenges of the Era of Society 5.0 to enrich chemistry learning as a need for a more meaningful life. The participants are 34 Grade X students from Natural Science Class 2 of Public High School (SMA NEGERI) 18 Jakarta. The data are pretest by Likert Scale Questionnaire, and posttest by a simple chemistry learning module with topic acid-base equilibrium. Keywords: Society 5.0; need for self-esteem; chemistry.